Activity of Na+/K+-ATPase in model lipid membrane at air-water interface. (10th May 2019) - Matyszewska, Dorota; Zatloukalova, Martina; Bilewicz, Renata
Abstract: The Na + /K + -ATPase pump was reconstituted in proteoliposomes composed of DPPC:DPPE, which were then spread at the air-water interface using Langmuir technique. In the presence of the enzyme in the liposomes the resulting lipidic layer at the air-water interface became more liquid. The effect of Na + /K + -ATPase on the morphology of Langmuir lipidic layers was monitored by Brewster angle microscopy, which showed the formation of lattice-like structure in between round-shaped lipid domains. The presence of protein stabilized the DPPC:DPPE mixed monolayer at the air-water interface, which was revealed by surface pressure measurements in time and ascribed to hydrogen bond network formation between the protein and the lipids. The activity of the protein embedded in the lipidic Langmuir layer was measured using spectroscopy and voltammetry. Free phosphate released from ATP reacted with ammonium molybdate and the blue α-Keggin anion formed was detected spectrophotometrically at a wavelength of 710 nm. The results based on spectroscopic assay were complemented with electrochemical methods. The activity of the enzyme could by switched off using the inhibitor – ouabain. The Na + /K + -ATPase activity (2.62 nmol mg −1  min −1 ) was similar to the activity of the protein solubilized using detergents (3.21 nmol mg −1  min −1 ). The slightly lower activity was ascribed to the defined orientation of the embedded protein molecules with respect to the air-water interface needed for its activity at the air–water interface. Graphical abstract: Image 1